Wide-range CTAT and PTAT sensors with second-order calibration for on-chip thermal monitoring. Issue 9 (September 2015) - Wang, Chua-Chin; Lu, Wen-Je; Wu, Tzu-Chao
Abstract This paper presents wide-range complementary to absolute temperature (CTAT) and proportional to absolute temperature (PTAT) sensors with second-order calibration for on-chip thermal monitoring. Particularly, a current mirror and an n-well resistor are used in these sensors to eliminate the second-order term of the temperature coefficient to linearize the transfer function between the output voltage and the temperature. The proposed CTAT and PTAT sensors are implemented on silicon using a typical 0.18 μm CMOS process. The core area of the CTAT and PTAT sensors is 0.0125 mm2 and 0.0074 mm2, respectively. In the range from <alternatives><inline-graphic xlink:href="ark:/27927/pgj2frffp9r" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />−55°C</alternatives> to <alternatives><inline-graphic xlink:href="ark:/27927/pgj2frfgbvw" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />155°C</alternatives>, the worst deviation of the CTAT and PTAT temperature sensors is measured to be <alternatives><inline-graphic xlink:href="ark:/27927/pgj2frfftnb" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />−3.75°Cto+3.34°C</alternatives> and <alternatives><inline-graphic xlink:href="ark:/27927/pgj2frfg8c4" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />−3.73°Cto+3.85°C</alternatives>, respectively. The maximum non-linearity reduction of the CTAT and PTAT sensors is 59.84% and 87.48%, respectively, by the proposed second-order calibration. Notably, the overhead area of the CTAT and PTAT sensors is only 0.64% and 1.08%, respectively.